MANAJEMEN DALAM KOMUNIKASI "PERSPEKTIF TEORI MANAJEMEN HENRY FAYOL” - Islami, Farina (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2024)
Management in communication is still very minimally practiced, in fact, not only does management require communication but communication also requires management. Management is not just an entity that requires communication, but communication itself also requires a management process to run more effectively. Previous research has mostly examined how communication plays a role in the management process, the effectiveness of communication in management, so this study aims to analyze the role of management in communication by applying the management theory perspective of Henry Fayol. The research used a literature review method with a conceptual approach, secondary data sources were obtained from journals, books, documentation, and articles related to the topic used. The results of the study show that management in communication can help minimize the risk of information failure and minimize communication barriers. Henry Fayol's management theory can have a positive impact on communication by making it more planned, structured, effective, and efficient.